All New on the European Front? What the Bologna Process Means for Translator Training in Germany - Nord, Christiane (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractAfter giving a brief survey of traditional translator training in Germany, the paper will discuss the changes introduced by the Bologna process. All German universities are reorganizing their translator training programmes, replacing the four-year Diplom degree by modular courses leading to a Bachelor’s and/or Master’s degree. Since legal regulations permit a variety of combinations with regard to duration, each German university is planning its own model. The main bone of contention in this process is the question of whether specialized translation should be taught at undergraduate or postgraduate level.